Sifat Fotoluminisensi Nanokomposit ZnO/GQD (Grafen Quantum Dot) - Zelin, Hikmatul Gusti Fadhia; Astuti, Astuti (Jurnal Ilmu Fisika, 2025)
The synthesis of ZnO/GQD nanocomposites aims to increase ZnO photoluminescence by conjugating techniques with other luminescent materials, namely graphene quantum dot (GQD). This material is applied as a bioimaging material. ZnO nanoparticles were conjugated with variations of GQD, namely (0.001 g, 0.0015 g, 0.002 g) by hydrothermal method. The results of characterization of ZnO/GQD nanocomposites using XRD show the formation of a hexagonal wurzite structure of ZnO, there is no change in the crystal structure of ZnO, while GQD has an orthorhombic crystal structure. Photoluminescence shows the highest visible light emission peak of ZnO nanoparticles at a wavelength of 620 nm which produces bright yellow luminescence. ZnO/GQD nanocomposites (0.001 g, 0.0015 g, 0.002 g) produced the highest photoluminescence peaks at wavelengths of 550 nm, 590 nm, and 580 nm, respectively. From the PL results, it can be concluded that there was an increase in the photoluminescence intensity with the addition of a small amount of GQD, namely 0.001 g, and there was a shift in the photoluminescence peak towards short wavelengths. This proves that the photoluminescence characteristics of ZnO can be controlled by conjugation with GQDs. Nanocomposites ZnO/GQD potential to be developed as bioimaging material.